A structure-activity relationship study of 1,2,4-triazolo[1,5-a][1,3,5] triazin-5,7-dione and its 5-thioxo analogues on anti-thymidine phosphorylase and associated anti-angiogenic activities - Bera, H.; Tan, B.; Sun, L.; Dolzhenko, Anton; Chui, W.; Chiu, G. (2013)
Thirty-three 1,2,4-triazolo[1,5-a][1,3,5]triazin-5,7-dione and its 5-thioxo analogues were designed and synthesized which contained different substituents at meta- and/or para-positions of 2-phenyl or 2-benzyl ring attached to the fused ring structure. The preliminary pharmacological evaluation demonstrated that the 5-thioxo analogues of 1,2,4-triazolo[1,5-a][1,3,5]triazine exhibited a varying degree of inhibitory activity towards thymidine phosphorylase, comparable or better than reference compound, 7-Deazaxanthine (7-DX, 2) (IC 50 value = 42.63 µM). Moreover, compounds 5q and 6i displayed a mixed-type of inhibitory mechanism in the presence of variable concentrations of thymidine (dThd). In addition, selected compounds were found to have a noticeable inhibitory effect on the expression of angiogenesis markers, including VEGF and MMP-9 in MDA-MB-231 breast cancer cells. © 2013 Elsevier Masson SAS. All rights reserved.